2016
DOI: 10.1097/hjh.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of longitudinal strain of subepicardial myocardium in patients with hypertension

Abstract: EpiLS was the only independent prognostic factor in regularly-treated hypertensive patients. Our results indicated that involvement of subepicardial myocardium may infer worse prognosis of hypertensive heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 25 publications
3
36
0
4
Order By: Relevance
“…However, the results from the studies that investigated LV multilayer strain are encouraging because they demonstrate a good predictive value of LV endocardial and epicardial strain. 10,11 Our findings confirm previous results regarding deterioration of cardiac autonomic nervous system in SSc patients. [12][13][14] However, more interesting is the relationship between HRV indices and RV parameters (global strain, layer-specific strain, and 3DE ejection fraction), as well as the association between Modified Rodnan Skin Score, HRV, and RV remodeling that have not been previously studied.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the results from the studies that investigated LV multilayer strain are encouraging because they demonstrate a good predictive value of LV endocardial and epicardial strain. 10,11 Our findings confirm previous results regarding deterioration of cardiac autonomic nervous system in SSc patients. [12][13][14] However, more interesting is the relationship between HRV indices and RV parameters (global strain, layer-specific strain, and 3DE ejection fraction), as well as the association between Modified Rodnan Skin Score, HRV, and RV remodeling that have not been previously studied.…”
Section: Discussionsupporting
confidence: 91%
“…Information about the predictive value of RV layer‐specific longitudinal strain is still unavailable. However, the results from the studies that investigated LV multilayer strain are encouraging because they demonstrate a good predictive value of LV endocardial and epicardial strain …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…T he observational study of Lee et al [1] investigated the prognostic value of global longitudinal strain (GLS), subendocardial and subepicardial longitudinal strain (EndLS and EpiLS, respectively) in regularly treated hypertensive patients after a mean follow-up of 7.3 years. Using multivariate Cox regression analysis, EpiLS was the only independent predictor of events and a cut-off point value of À17.57% distinguished the worse cardiovascular outcome in the population assessed.…”
mentioning
confidence: 99%
“…The novelty of the study of Lee et al [1] corresponds to the differential prognostic value showed by EpilS and EndLS. In fact, only EpiLS stratified the prognosis, independent of the impact of confounding factors.…”
mentioning
confidence: 99%